2020
DOI: 10.34172/jsums.2020.17
|View full text |Cite
|
Sign up to set email alerts
|

Study of anticancer activity of cecropin B on 7, 12-dimethylbenz (a) anthracene-induced breast cancer

Abstract: Background and aims: Antimicrobial peptides constitute a family of bioactive peptides that are involved in the body defense. Recently, their anti-cancer properties, especially by inducing apoptosis, have been proven in in vitro studies. Therefore, in this study, the effects of cecropin B as an antimicrobial peptide on breast cancer growth, hematological parameters, and histopathological changes in rats were evaluated. Methods: Twenty-four female rats were randomly divided into 4 groups. The cancer group, contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“… 15 , 103 , 104 According to Ghandehari et al, F. latex can reduce the number of mitotic abilities and the extent of apoptosis in breast cancer cells without affecting hematological or histological functions. 105 A study by Purnamasari et al, which evaluated the effects of F. carica leaf and fruit extracts treatment on Huh7it liver cancer cell line, reported that the percentage of apoptotic and necrotic cells increased with increasing concentrations of the extracts. 104 The highlight of the study is summarized in Table 6 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 , 103 , 104 According to Ghandehari et al, F. latex can reduce the number of mitotic abilities and the extent of apoptosis in breast cancer cells without affecting hematological or histological functions. 105 A study by Purnamasari et al, which evaluated the effects of F. carica leaf and fruit extracts treatment on Huh7it liver cancer cell line, reported that the percentage of apoptotic and necrotic cells increased with increasing concentrations of the extracts. 104 The highlight of the study is summarized in Table 6 .…”
Section: Methodsmentioning
confidence: 99%
“…A study by Khan et al claimed that F. carica -enriched plant extracts could be used to stimulate and enhance the rate of collagen biosynthesis and recover the hydration level of the dermis. 105 This phenomenon was postulated due to F. carica’s high level of antioxidant properties such as vitamin C, anthocyanins, carotenoids and phenolic compounds. 116…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Zhang et al (2018) reported that FC extract administration decreased the breast cancer marker gene (GATA3) and also had an impact on the expression of exprotooncogene (ELF5). Ghandehari and Fatemi (2018) reported that breast tumor volume and size decreased in rats treated with a latex extract of F. carica. Further, the histological study of fig latextreated rat breast cells showed a reduction in angiogenesis, mitotic features, & necrosis.…”
Section: Ficus Caricamentioning
confidence: 99%
“…It has a high content of several bioactive compounds, including phytosterols, amino acids, and fatty acids (Oliveira et al, 2010). Recent studies show that Ficus carica latex (FCL) exerts an inhibitory effect on the growth of various cancer cell lines (Ghandehari & Fatemi, 2018; Hashemi et al, 2011; Khodarahmi, Ghasemi, Hassanzadeh, & Safaie, 2011). Tezcan et al (2015) reported that FCL is a potential antitumor agent and inhibits tumor growth via regulation of miR‐let‐7d and reduces invasion in T98G, U138 MG, and U87MG cell lines.…”
Section: Natural Products and Mirnas In Glioma Therapymentioning
confidence: 99%